2019
DOI: 10.26682/ajuod.2019.22.2.3
|View full text |Cite
|
Sign up to set email alerts
|

Development of A Combined Insect Trap for Whitefly (bemisia Tabaci) And Tomato Leaf Miner (tuta Absoluta) Management

Abstract: Whitefly Bemisia tabaci and tomato leaf miner Tuta absoluta are two important insects that are causing serious damage to crops in protected vegetable cultivation. There is an international call from scientists to find a non-chemical way to manage those pests. This study tested the effect of a new combined light trap with different colors, named GLT trap, on the management of whiteflies and tomato leaf miners in protected vegetable cultivation. The results showed that whiteflies are significantly attracted to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
(26 reference statements)
1
0
0
Order By: Relevance
“…The efficacy of five insecticides from different groups was tested under laboratory conditions on all stages of TLM, the results showed that spinosad was the most effective against the stages of the pest [42]. This agrees with what [43] found that treating TLM pupae with the fungicide B. bassiana led to a decrease in the percentage of adult emerging from pupae, the increase of the concentration, caused the lower percentage of the emergence of adults, this also affects the biological characteristics of the insect, as the insects that emerged from the pupa are treated with the high concentrations of fungicide, it cannot lay eggs, as well as shortening the lifespan of the adult insect. [44] found in their study the evaluation of some commercial EPF, B. bassiana (Bals.)…”
Section: Percentage Of Emergence Of Adults From Tlm T Absoluta M Pupa...supporting
confidence: 71%
“…The efficacy of five insecticides from different groups was tested under laboratory conditions on all stages of TLM, the results showed that spinosad was the most effective against the stages of the pest [42]. This agrees with what [43] found that treating TLM pupae with the fungicide B. bassiana led to a decrease in the percentage of adult emerging from pupae, the increase of the concentration, caused the lower percentage of the emergence of adults, this also affects the biological characteristics of the insect, as the insects that emerged from the pupa are treated with the high concentrations of fungicide, it cannot lay eggs, as well as shortening the lifespan of the adult insect. [44] found in their study the evaluation of some commercial EPF, B. bassiana (Bals.)…”
Section: Percentage Of Emergence Of Adults From Tlm T Absoluta M Pupa...supporting
confidence: 71%